ANALISIS KINERJA RUAS JALAN TAN MALAKA (SEGMEN PASAR DANGUNG – DANGUNG) KABUPATEN LIMA PULUH KOTA - Kholis, Alfin; Yermadona, Helga; Endri, Endri (Ensiklopedia Research and Community Service Review, 2024)
Dangung-dangung market is located on Jalan Tan Malaka, Limapuluh Kota Regency, which has a heavy traffic volume coupled with high side obstacles due to parking on the road and traders on the shoulder of the road. The aim of this research is to provide alternative suggestions for improving the performance of sections on the Tan Malaka road. From the results of the performance analysis for the performance of road sections in existing conditions, namely, the degree of saturation in existing conditions, precisely on market days, is 0.84 with a service level of "D", for the average market speed, namely 21.45 km/hour with a service level ”E”. There was an increase in the performance of the section on Jalan Tan Malaka after alternative proposals were made by moving on-street parking to off-street, providing pedestrian facilities, structuring traders and installing road equipment and infrastructure facilities along Jalan Tan Malaka. This can be seen from the road capacity which increased from 1342 pcu/hour to 2470 pcu/hour, experienced an increase in speed from 21.45 km/h to 39 km/h, decreased the degree of saturation from 0.84 to 0.46.Keywords: Side Obstacles, Degree of Saturation, Speed, Traffic Volume, Market.